Middle Landscapes: exploring the degrees of retreat through a seaport at Durban habour - Hart, Tamsyn (My University, 2016)
“People love escapism and there should be a place for it” (Hiddleston, n.d.) There are two primary states that constitute our human experiences. On the one side, there is the known, the real, the concrete, the everyday, the routine, normal and banal aspects of human life and on the other, the imagined, the alternative, the exploratory, unknown, abstract and fantastical elements that arguably make us feel alive. Although these two phenomena are preconceived as separate entities, they are interdependent and as humans, we need both. In the midst of these two extremities lies a world of in-between spaces known as ‘middle landscapes’. These are the places that allow us to transition between two states that make up our human experiences. Herein lies the bridge from the known to the unknown and the connection between reality and retreat. In a world where the demands of work are taking an increasing toll on our time and energy, the middle landscapes constitute our means of escape; the process that enables us to retreat from reality. The city of Durban in Kwa-Zulu Natal is a thriving cosmopolitan metropolis with a large array of places focused on diversion from reality. Its enviable connection with the sea and expansion of the tourist industry are the bones of its potential to become a 21st century escapist city; a place where people are encouraged to retreat. The exploration and adventure found on the edges of the ocean attract many to its shorelines, seeking distraction, diversion, retreat and escape. There is something about the mystery of the sea, the unquantifiable majesty of its waters that lures us in, allowing us to be drawn away from our everyday lives and to give in to rest, relaxation and holiday before the grasp of the real pulls us back. How can architecture provide a transition between everyday life and retreat, between land and sea? This thesis seeks to explore the role of architecture in connecting people to the ultimate place of escape, the sea, through a seaport at Durban Harbour. The building, sited in the Point Area of Durban Harbour, will provide a connection with the sea and the retreat it embodies at a variety of different scales. It will reconnect the CBD with the Point, the beachfront with the harbour and give the citizens of Durban a refuge from the real while meeting an urgent need for a new cruise passenger terminal and activating the Point Waterfront Development. The building will become the middle landscape, sited on the boundary between land and sea, meeting the practical needs of the city and the tourist industry while providing for the leisure needs of Durban’s people. Whilst displaying sensitivity to the existing harbour architecture and context, the building will become a recognisable beacon for the city, visible from shoreline and sea.
Thesis (M.Arch. (Professional))--University of the Witwatersrand, Faculty of Engineering and the Built Environment, 2016.
Keywords: City planning--South Africa--Durban; Public spaces--South Africa--Durban; Harbours--South Africa--Durban